Phase I study of trametinib in combination with whole brain radiation therapy for brain metastases. (May 2022) - Palmer, Joshua D.; Prasad, Rahul N.; Fabian, Denise; Wei, Lai; Yildiz, Vedat O.; Tan, Yubo; Grecula, John; Welliver, Meng; Williams, Terence; Elder, James B.; Raval, Raju; Blakaj, Dukagjin; et al.
Highlights: Trametinib is a MEK inhibitor with intracranial activity used for BRAF+ disease. Even subtherapeutic trametinib doses are toxic with whole brain radiation therapy. The overall response rate was 33% with a median survival of 2.2 months. Abstract: Introduction: Trametinib is a MEK inhibitor with intracranial activity indicated for BRAF-mutant metastatic malignancies. Yet, the safety of trametinib concurrent with whole brain radiation therapy (WBRT) is unknown. We performed a single-institution, prospective, 3 + 3, phase I clinical trial to determine the maximum tolerated dose (MTD) of trametinib with WBRT. Methods and Materials: Patients with brain metastases (BM) received daily trametinib for 28 days, starting 7 days prior to and continuing through WBRT (37.5 Gy/15 fractions). Dose levels (DL)1–3 were 1.0, 1.5, and 2.0 mg. The MTD of trametinib plus WBRT, the max dose where ≤1 of 6 patients experienced a dose limiting toxicity (DLT), was the primary endpoint. Results: 10 patients were enrolled (median age-59 [47–64], BM-5 [1–10], 50% melanoma). Three and 7 patients were assigned to DL1 and 2. One DL2 patient withdrew. 89% of remaining patients completed therapy per protocol, but 1 DL2 patient with systemic progression discontinued therapy at 30 Gy. Thirteen grade (G)3–4 toxicities were observed, of which 12 occurred at DL2 (4/6 of patients). DLT was reached at DL2 (G4 thrombocytopenia and G3 diarrhea, 1 each). There were no G5 toxicities. Median overall survival was 2.2 months. During the study period, changing practice patterns favored utilization of stereotactic radiosurgery (SRS). Thus, the trial closed early prior to completion. Conclusions: In a patient population representative of modern candidates for WBRT, trametinib plus WBRT is highly toxic with a MTD <1.5 mg. The safety of trametinib with SRS remains an important question for future study.